Enhancing hydrogen production from biomass pyrolysis by dental-wastes-derived sodium zirconate. (6th September 2019) - Wang, Fan; Wang, Ping; Raheem, Abdul; Ji, Guozhao; Memon, Muhammad Zaki; Song, Yinqiang; Zhao, Ming
Abstract: Sodium zirconate was synthesized via the solid-phase reaction from dental wastes with sodium carbonate. The dental-wastes-derived sodium zirconate (DW-SZ) dramatically enhanced hydrogen (H2 ) production during biomass pyrolysis due to the presence of alkali metal (Na) and in-situ carbon dioxide (CO2 ) capture. To be specific, the DW-SZ could maintain a maximum CO2 uptake of 0.195 g-CO2 g-sorbent −1 at the 30th cycle under cyclic CO2 absorption/desorption swings. The total CO2 uptake in all 30 cycles reached 82% of the theoretical CO2 uptake. The synthesized functional material was subsequently employed for H2 production in the pyrolysis of three different biomass samples (i.e., municipal sludge, spirulina, and methylcellulose). The highest H2 yield of 205 ml g −1 was produced by spirulina in presence of functional material, followed by methylcellulose (197 ml g −1 ), and municipal sludge (142 ml g −1 ). Moreover, the DW-SZ was characterized by XRD, BET and SEM to help unravel and justify the underlying reaction mechanisms. Highlights: Dental-wastes-derived sodium zirconate was synthesized as bifunctional material. DW-SZ dramatically enhanced H2 production during biomass pyrolysis. The synthesized DW-SZ showed superb cyclic stability over 30 cycles.